Monetary policy in a world of cryptocurrencies - Pierpaolo Benigno (University of Bern, Department of Economics, 2022)
Can currency competition affect central banksícontrol of interest rates and prices? Yes, it can. In a two-currency world with competing cash (material or digital), the growth rate of the cryptocurrency sets an upper bound on the nominal interest rate and the attainable inflation rate, if the government currency is to retain its role as medium of exchange. In any case, the government has full control of the inflation rate. With an interest-bearing digital currency, equilibria in which government currency loses medium-of-exchange property are ruled out. This benefit comes at the cost of relinquishing control over the inflation rate.
Keywords: 330